2016
DOI: 10.1007/s00246-016-1352-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Low-Shear Blood Viscosity is Associated with Decreased Pulmonary Blood Flow in Children with Univentricular Heart Defects

Abstract: After the Fontan procedure, patients with univentricular hearts can experience long-term complications due to chronic low-shear non-pulsatile pulmonary blood flow. We sought to evaluate hemorheology and its relationship to hemodynamics in children with univentricular hearts. We hypothesized that low-shear blood viscosity and red blood cell (RBC) aggregation would be associated with increased pulmonary vascular resistance (PVR) and decreased pulmonary blood flow (PBF). We performed a cross-sectional analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Although the precise mechanism of RBC aggregation is still not explored, several factors, including fibrinogen or RBC cell age have been described to affect RBC aggregation: Previous studies demonstrated increased RBC aggregation due to higher concentrations of fibrinogen (Varlet-Marie et al, 2003; Simmonds et al, 2013). The results presented here did not show differences in aggregation between Fontan patients and healthy controls, which is in concordance to previous findings of Cheng et al (2016). Also, fibrinogen levels were comparable between the groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the precise mechanism of RBC aggregation is still not explored, several factors, including fibrinogen or RBC cell age have been described to affect RBC aggregation: Previous studies demonstrated increased RBC aggregation due to higher concentrations of fibrinogen (Varlet-Marie et al, 2003; Simmonds et al, 2013). The results presented here did not show differences in aggregation between Fontan patients and healthy controls, which is in concordance to previous findings of Cheng et al (2016). Also, fibrinogen levels were comparable between the groups.…”
Section: Discussionsupporting
confidence: 92%
“…Morphological alterations of vasculature were previously described in Fontan patients with higher arterial stiffness and increased intima-media-thickness, resulting in shear-stress changes (Lambert et al, 2013; Ridderbos et al, 2015). This might have an impact on hemorheology, even though no differences in RBC aggregation and deformability were demonstrated in 20 Fontan patients compared to ASD patients in a previous study (Cheng et al, 2016).…”
Section: Introductionmentioning
confidence: 75%
“…Even with a non-Newtonian effect, one can easily use non-Newtonian models to adjust Equation (23), e.g. Cheng et al 4 .…”
Section: Discussionmentioning
confidence: 99%
“…A non-Newtonian important factor ( I L = μ eff /μ , where μ eff is the effective viscosity) was introduced to determine the non-Newtonian effect, and the cut-off value was suggested to be 1.75 16 . In order to estimate μ eff , this study plugged the shear rate from the simulation to a Carreau model which curve-fitted experimental data from Cheng et al 4 . One case, in this study, exhibited an I L slightly above the cut-off line, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It mainly affects the viscosity and patency of blood in microcirculation. The changes of rheological property of red blood cells will result in the increase of the viscosity and patency of blood, decrease of microcirculation function, reduction of returned blood volume, decrease of cardiac output and insufficiency of organ perfusion, which finally leads to organ failure 11,12. In addition, the increased blood viscosity will increase the risk of thrombosis.…”
Section: Discussionmentioning
confidence: 99%